REKONSTRUKSI PERAN PEREMPUAN DALAM REVOLUSI INDUSTRI MELALUI SUMBER-SUMBER TERTULIS - Winnie Nashorunnisa Pohan; Hani Yasmin Kuseni; Reza Reza; Sabila Mandawati; Tiara Murni Febriana (Department of History Education, Faculty of Social Science, Universitas Negeri Medan, 2024)
This research is motivated by the phenomenon of the development of the role of women in the industrial revolution sector. Although the role of women has a huge impact in Indonesia, there are still various challenges that must be faced in strengthening the potential role of women in the Industrial Revolution era. This research method uses a case study with a qualitative approach. This research uses purposive sampling method and data collection techniques such as in-depth interviews with resource persons. The results in this study show that nowadays there have been many considerable changes in work activities, especially for productive work in addition to reproductive/domestic work. Women have been involved in many productive jobs or work for a living. However, women's involvement in income-generating work activities still appears to be closely related to the existing employment structure in society. As in production, there are generally different assessments of men's work and women's work, especially with regard to technology. Since technology is often patriarchal, men tend to have more access to it than women. However, there has been a shift in work roles from women doing reproductive work to productive work. Women are starting to do more agricultural work, large and small industries and various fields of development that produce economic value.